Relationship between Narcissism, Body Image and Instagram Usage - Mubara Younas, Ahmed Bilal, Hifza Imran, Ghuncha Naqvi, Ifzonia Babar, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the relationship between narcissism and body image with Instagram usage. Methodology: This cross-sectional research study was conducted in three Universities of Lahore; The university of Lahore, University of Management and Technology, and University of Central Punjab. 200 university students were taken including 100 females and 100 males. age, gender. Narcissistic Personality Inventory-16, Body appreciation Scale-2 (BAS-2), Motive for Instagram use were employed, their age, education, birth order, economic status and student’s qualification were used. Results: The results showed that there was a positive significant relationship between narcissism and body image. More results also revealed a positive relationship regarding narcissism and the usage of Instagram. Conclusion: Narcissism and body image are correlated that means the individuals who have narcissist features, they mentor themselves and have self-image, self-concept, self-perception and outer appearance in their mind and they spend more time on Instagram and are more concerned about their physical appearance.